Influência da alteração da distribuição do tamanho de partículas do desempenho de reatores UASB tratando esgotos domésticos - Ana Raquel Teixeira (2007)
The core of this work is the development of a new concept of pre-treatment that uses the forced sieving of raw sewage as a strategy to reduce the average size of the particles and increase the conversion rates of particulate material in UASB reactors, used for treatingdomestic wastewater. The experimental apparatus consisted of two identical UASB reactors, one of them preceded by a 1mm mesh metallic sieve. Both reactors were operated under different hydraulic load conditions, with variation in hydraulic retention times and upflowvelocities. The performance of the reactors was evaluated considering the usual parameters (COD, solids and SMA). Analysis of the particle size distribution was performed with samples of raw and sieved sewages to verify the effectiveness of the pre-treatment in reducing the particulate material. The conversion rates of particulate material present in the raw sewage were obtained from hydrolysis tests. The forced sieving resulted in a higher concentration of particles with diameter range of 1,8 and 30 m in the reactor influent. However, the reduction in the particles size range was not enough to increase the particulate material hydrolysis rates, since the first order relation kinetics, used to describe the process, leaded to hydrolysis constants values of 0.0446 ±0.0104 d-1, for the raw sewage, and of 0.0472 ± 0.0079 d-1, for the sieved sewage, when evaluated VSS decay. However, the reduction in the particles sizeresulted in a biomass with higher activity and, apparently, with better settleability characteristics, after the microbial community adaptation, selection and growth. The specific methanogenic activity (SMA) value of the sludge from the reactor preceded by the forced sieving unit (0,31 g COD.g VS-1.d-1) was higher than the result of the sludge from the controlreactor (0,18 g COD.g VS-1.d-1), when the reactors were operated under adverse conditions (HRD = 5 h and upflow velocities = 1.10 m.h-1). Thus, although the conversion rates of particulate material in the raw and sieved sewage were similar, the development of a biomass with higher activity provided better performance of the UASB reactor, increasing theefficiency in the removal of total COD (65% for the reactor preceded by the forced sieving unit, versus 54% for the control reactor), and producing an effluent with lower particulate COD concentration (48 mg.L-1 versus 74 mg.L-1).